PENGARUH METAKAOLIN SEBAGAI PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN BETON RINGAN - Sultan Aditya Ananda Dalimunthe; Denny Meisandy Hutauruk (Matriks Teknik Sipil, 2025)
Abstract- Sultan Aditya Ananda Dalimunthe: Effect of Metakaolin as a Partial Replacement of Cement on the Compressive Strength of Lightweight Concrete. Undergraduate Thesis. Faculty of Engineering, State University of Medan. 2025. With the rapid advancements in concrete technology within the construction industry, lightweight concrete has emerged as a highly promising alternative material, offering significant functional and practical benefits. Prior research indicates that adding metakaolin substantially enhances concrete's strength and durability compared to standard mixtures, demonstrating its positive impact on the mechanical properties of concrete. This study investigates the effect of metakaolin on the compressive strength and specific gravity of lightweight concrete. The experimental research was conducted at the Concrete Laboratory of the Faculty of Engineering, Universitas Negeri Medan. Four variations of metakaolin content (12.5%, 15%, 17.5%, and 20% by weight of cement) were tested to determine the compressive strength (in accordance with SNI 1974-2011) and specific gravity (using a weighing method) of the lightweight concrete. The results show that the optimum compressive strength for lightweight concrete, reaching 11.9 MPa, was achieved with a 20% metakaolin addition. This value meets the compressive strength requirements of lightweight structural lightweight concrete (6,89-17,24 MPa) according to SNI 03-3449-2002. Furthermore, the highest specific gravity of lightweight concrete (1787,23 kg/m3) was also observed at 20% metakaolin content, falling within the standard range for structural lightweight concrete specified by SNI 03-3449-2002 (1400-1850 kg/m3). In conclusion, this research indicates that increasing the percentage of metakaolin in lightweight concrete mixtures significantly improves both its compressive strength and specific gravity. Keywords: compressive strength; lightweight concrete; metakaolin; specific gravity.